The effect of fuel additive SO‐2E on diesel engine performance when operating on diesel fuel and shale oil - Labeckas, Gvidonas; Pauliukas, Arvydas; Slavinskas, Stasys (Transport, 2006)
The purpose of this research is to perform comparative analysis of the effect of fuel additive SO‐2E on the economical and ecological parameters of a direct‐injection Diesel engine, operating on Diesel fuel and shale oil alternately. It was proved that multifunctional fuel additive SO‐2E applied in proportion 0,2 vol % is more effective for improving combustion of shale oil than Diesel fuel. At light operation range the treated shale oil savings based upon fuel energy content throughout wide speed range 1400–2000 min−1 reduce from 14,6–12,3MJ/kWh to 11,6–11,8 MJ/kWh or by 20,5–4,1 %. Maximum NO emission for treated Diesel fuel was reduced by 7,8–11,8 %, whereas NO2 simultaneously increased by 3,8–7,4 %. In the case of treated shale oil both harmful pollutants were reduced by 22,9–28,6 % and by 41,6–13,4 %, respectively. The exhaust gas opacity and CO emissions at the rated performance regime for both fuels were obtained a bit higher, whereas HC emission for treated shale oil increases 1,9 times and for Diesel fuel remains on the same level.First Published Online: 27 Oct 2010